Perspective Taking and Avatar-Self Merging - Müsseler, Jochen; von Salm-Hoogstraeten, Sophia; Böffel, Christian (Frontiers in Psychology, 2022)
Today, avatars often represent users in digital worlds such as in video games or workplace applications. Avatars embody the user and perform their actions in these artificial environments. As a result, users sometimes develop the feeling that their self merges with their avatar. The user realizes that they are the avatar, but the avatar is also the user – meaning that avatar’s appearance, character, and actions also affect their self. In the present paper we first introduce the event-coding approach of the self (Hommel, 2017) and then argue based on the reviewed literature on human-avatar interaction that a self-controlled avatar can lead to avatar-self merging: the user sets their own goals in the virtual environment, plans and execute the avatar's actions, and compares the predicted with the actual motion outcomes of the avatar. This makes the user feel body ownership and agency over the avatar’s action. Following the event-coding account, avatar-self merging should not be seen as an all-or-nothing process, but rather as a continuous process to which various factors contribute, including successfully taking the perspective of the avatar. Against this background, we discuss affective, cognitive, and visuo-spatial perspective taking of the avatar. As evidence for avatar-self merging, we present findings showing that when users take the avatar's perspective, they can show spontaneous behavioral tendencies that run counter to their own.